A new genus of Pachybrachini from Bolivia (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2025)
Griburella gen. nov. is described from Central Bolivia, with Griburella sanctaecrucis sp. nov. as the sole species belonging to it. The new taxon superficially resembles certain forms of the polymorphic (and likely polyphyletic) genus Griburius Haldeman, 1849 but no species of the latter, nor any Pachybrachini known up to now, has appendiculate claws, as observed in Griburella gen. nov. The latter also differs from Griburius in its narrow and elongated prosternal process, the absence of the typical thickening of the forelegs in males, and the presence of extremely dense and regularly spaced punctation on both the elytra and the pronotum. Notably, no indication of true elytral striae formation is observed on the elytra.